Validity of the German version of the Stay Independent Questionnaire applied by telephone interview: A diagnostic accuracy study - Ulrich Thiem; Ingeborg Schlumbohm; Stefan Golgert; Ulrike Dapp; Saskia Otte (PLoS ONE, 2025)
Background Mobility limitations are among the most common functional problems in older people. Repeated falls can lead to injuries and fractures, trigger or intensify concerns of falling, and contribute to subsequent functional decline and loss of independence. Various questionnaires have been developed, both nationally and internationally, to identify older people at increased risk of falling. Data for evaluation against standard tests from the geriatric mobility assessment are scarce. Methods In a German project evaluating home emergency call systems, the Stay Independent Questionnaire (SIQ) from the American prevention program STEADI (Stopping Elderly Accidents, Deaths, and Injuries) was used for the identification of community-dwelling seniors aged 70 and older at risk of falling. The original questionnaire was translated by professional translators using the typical forward and backward translation process, and a final version was established after discussion involving a bilingual scientist. The diagnostic performance of the questionnaire (diagnostic test) was tested against the mobility assessment Short Physical Performance Battery (SPPB, gold standard). To describe the test performance, typical statistical measures are used, i.e., sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios, each with the corresponding 95% confidence interval (95% CI). Results Data from a total of 190 participants (143 women, 75.3%; average age 80.5 years ± 5.5 years standard deviation) were included in the analysis. According to existing comorbidities and functional abilities, between 30% and 40% suffered of advanced comorbidity and/or functional impairment. The questionnaire identified 148 individuals (77.9%) as at risk of falling. According to SPPB, 81 participants had an objectively measurable impairment of standing and walking balance. The test performance measures for SIQ as a diagnostic test are: sensitivity 95.1% 95% CI [88.0%; 98.1%], specificity 34.9% [26.6%; 44.2%], positive and negative predictive value 52.0% [44.0%; 59.9%] and 90.5% [77.9%; 96.2%], respectively, and positive and negative likelihood ratio 1.46 [1.26; 1.69] and 0.14 [0.05; 0.38]. In receiver-operating characteristic (ROC) analysis, the unadjusted area under the curve for SIQ was 65.0% [57.3%; 72.7%], after adjustment for sex and age 71.0% [63.8%; 78.2%]. Conclusions The German version of the Stay Independent Questionnaire is capable of identifying community-dwelling seniors aged 70 and older without impairment in standing and walking balance. The high sensitivity of the test allows excluding test-negative individuals from further investigation. A limitation of the questionnaire is the high proportion of false positives, resulting from the low specificity of the test. Scientific evaluation will show to what extent the use of the questionnaire may improve the identification and medical care of community-dwelling seniors at risk of falling in terms of fall prevention.